1999
DOI: 10.1107/s0907444998008208
|View full text |Cite
|
Sign up to set email alerts
|

On `globbicity' of low-resolution protein structures

Abstract: Using Harker's [Harker (1953). Acta Cryst. 6, 731±736] idea of spherically averaged polyatomic groups or`globs' as the units of structure suitable for analyzing low-resolution diffraction data from protein crystals,`globbic' scattering factors have been calculated for main-chain peptide units and amino-acid side-chain groups to 3 A Ê resolution via Debye's [Debye (1915). Ann. Phys. (Leipzig), 46, 809±823] scattering formula. It is shown that the scattering factors are insensitive to intra-globbic conformationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 10 publications
2
25
0
Order By: Relevance
“…At the particular value of t = 1.5 bohr 2 , fragments are similar to the groups of atoms used by Guo et al [5] in their globbic description of a protein structure. An interest of such decomposition results lies in the possible link with ED map interpretation programs based on the use of protein fragments databases.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…At the particular value of t = 1.5 bohr 2 , fragments are similar to the groups of atoms used by Guo et al [5] in their globbic description of a protein structure. An interest of such decomposition results lies in the possible link with ED map interpretation programs based on the use of protein fragments databases.…”
mentioning
confidence: 55%
“…MoPro implements spherical and multipolar atomic models, and combines methods usually applied both in biological macromolecules and in small compounds crystallography fields. We will also present some applications of these methods to several macromolecular systems, including 0.66Å resolution Human Aldose Reductase [3,4] and 0.62Å resolution RD1 Antifreeze protein [5]. A theoretical method applied to describe protein structures in terms of hierarchically related substructures is presented [1].…”
mentioning
confidence: 99%
“…For the lower-resolution structures the density maxima often do not correspond to atomic positions but should rather be associated with atomic groups. For example, at @3-Å resolution, we and others have shown that for protein crystallography there is a correspondence between ED peaks and the backbone or side-chain atoms of the amino acid residues [1][2][3]. For example, Guo et al [2] showed that 3-Å resolution ED distributions could be reconstructed from structure factors generated by residue centers.…”
mentioning
confidence: 99%
“…The scale of this phasing procedure can vary greatly, from simulation of the overall protein mass distribution (Andersson & Hovm611er, 1996) to generalized scattering factors for amino acid segments (Guo et al, 1995). In electron crystallography, it has been observed that the projection of a helical column might also be treated as a pseudoatomic glob (Dorset, 1997a).…”
Section: Introductionmentioning
confidence: 99%